The acquisition of French in different contexts : focus on functional categories - Prévost, Philippe, 1966-; Paradis, Johanne (Language acquisition & language disorders, 2004)
This volume is a collection of studies by some of the foremost researchers of French acquisition in the generative framework. It provides a unique perspective on cross-learner comparative research in that each chapter examines the development of one component of the grammar (functional categories) across different contexts in French learners: i.e. first language acquisition, second language acquisition, bilingual first language acquisition and specifically-language impaired acquisition. This permits readers to see how similar issues and morphosyntactic properties can be investigated in a rang.